Barriers and Cross Cultural Communication Challenges: The Insights Indonesian International Student Mobility Awards (IISMA) 2022 Awardees at Phoenix Academy - Kaulika, Arabella; Simanjuntak, Tiur; Agustina Sari, Evi; Ridhwan, Moehamad; Zulkifli, Zulkifli (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This article was written with the purpose of investigating the cross-cultural communication barriers experienced by Indonesian International Student Mobility Awards (IISMA) for Vocational Students 2022 awardees at Phoenix Academy during their time studying in Perth, Australia, as well as their solutions to overcome said barriers. Aligned with the research’s objectives and subjects, the method used in conducting this research is the qualitative method. The writer conducted a series of in-depth interviews with 14 (fourteen) IISMA for Vocational Students 2022 awardees at Phoenix Academy. The writer found the six main barriers they had been subjected to during their stay based on the theory by Kiss (2005): different communication styles, different attitudes towards conflicts, different approaches to completing tasks, different decision-making styles, different attitudes towards disclosure, and different approaches to knowing. The writer concluded that their strategies to overcome each barrier varied according to the awardees’ personal approach and causes. Thorough analysis of the data was performed by dissecting the awardees’ experiences, interpreting their opinions, and correlating them with the relevant theory. It is aimed for this article to be able to aid the future batches of IISMA awardees or recipients of other international programs.